Low cost surge protective device for communication and data line systems. - Ab Kadir, Mohd Zainal Abidin; Rameli, Norhidayu (2011)
The present invention discloses a low cost surge protective device that is designed in accordance with the MS IEC 61643-22 standard for use in the protection of telecommunication equipment from electrical transients. The low cost surge protective device of the present invention comprises of two stages, a first stage and a second stage. The first stage comprising of a pair of Gas Discharge Tubes (GDT), that are respectively connected in between the Ring line and ground line, and the Tip line and ground line. The second stage comprises of two pairs of zener diodes. Each pair of zener diodes in the second stage are interconnected such that the cathodes of each of said pair of zener diodes face each other in opposition, whereas the anode of one zener diode of said pair of zener diodes connects to the ring or tip line and the anode of the other zener diode of said pair of zener diodes connects to the ground line.